2021
DOI: 10.1002/dys.1705
|View full text |Cite
|
Sign up to set email alerts
|

Saudi public primary school teachers' knowledge and beliefs about developmental dyslexia

Abstract: This exploratory research investigates knowledge and beliefs about developmental dyslexia (DD) among public primary school teachers in Saudi Arabia. We explored links between several teacher‐related socio‐demographic variables (e.g., gender, teaching experience, self‐evaluation of teaching children with DD) and knowledge and beliefs about DD. Saudi public primary school teachers (n = 136) completed an online survey that included the knowledge and beliefs about developmental dyslexia scale (KBDDS). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…23 The Arabic version this instrument was used. 24 This tool consists of three sections and 39 questions were developed to investigate ADHD, characteristics and ways of treatment (12 questions). The answers for each question are True, false, or Do not Know.…”
Section: Instrumentsmentioning
confidence: 99%
“…23 The Arabic version this instrument was used. 24 This tool consists of three sections and 39 questions were developed to investigate ADHD, characteristics and ways of treatment (12 questions). The answers for each question are True, false, or Do not Know.…”
Section: Instrumentsmentioning
confidence: 99%
“…According to Dodur and Kumas, a survey conducted between 2019 and 2020 involving 260 teachers aged 28 to 59 from 3 to 37 years of experience from 25 primary schools came to the same conclusion. According to Abed and Shackelford (2021), the survey conducted in Jeddah, Saudi Arabia, involved 136 primary public school teachers through an online survey, and the result showed that teachers who had 11 to 20 years of work possessed more knowledge than those with fewer or more years of work. Also, dyslexia is not widely recognized in Saudi Arabia, resulting in no academic training.…”
Section: Presentation Of Relevant Research Findingsmentioning
confidence: 99%
“…Then, in the rest of the questionnaire, which consists of thirty (30) questions, participants fill in the answers representative for them. The questions concern teachers' knowledge of dyslexia detection (5,8,10,14,21,23,25,28,27,30) [Research question 1], teachers' knowledge of differentiated teaching (1,2,4,7,11,13,16,18,20,29) [Research question 2] and their choice for further training (3,6,9,12,15,17,19,22,24,26)…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will continue to grow if the early detection and management of dyslexia are not given full attention by people from different fronts who are both directly and indirectly involved in it. In Saudi Arabia itself, the percentage of incidence has already reached 7% and, as such, efforts are being made to detect the disorder early, so that management and preemptive measures are in place and on time [ 2 ]. Dyslexia is a disorder of a neurological origin that affects the learning of those who suffer from it.…”
Section: Introductionmentioning
confidence: 99%